(untitled) (Itinera, 2024)
The sermons of Pier Damiani (1007-1072), generally little investigated by scholars, can offer interesting insights also to those who read them from a philosophical (since they contain some argumentative structures, beginning with the comparatio) and rhetorical point of view. In particular, references to memoria can be detected in many of them: for example, the entire Sermo II de translatione sancti Hilarii is structured around the theme of remembrance. In general, it can be observed that the evocation of a biblical character, and his actions, is an occasion for a connection with the saint and the events being discussed in the homily. In this way Pier Damiani emphasizes the continuity of salvation history, which is operative in the remote Old Testament past as well as in his contemporary, and from this he draws basic moral lessons.